2011
DOI: 10.1152/ajpgi.00329.2010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with IL-27 attenuates experimental colitis through the suppression of the development of IL-17-producing T helper cells

Abstract: Inflammatory bowel disease (IBD) represents a group of chronic inflammatory diseases characterized by inflammation and relapsing gastrointestinal disorders. Recent studies have shown that Th17 cells, which are well known as key mediators of chronic inflammation, have a pivotal role in onset and development of IBD in humans and mice, alike. In recent years, it has been reported that IL-27, which is an IL-12-related heterodimeric cytokine consisting of EBI3 and p28 subunits, act directly on naive T cells to supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 46 publications
3
47
1
3
Order By: Relevance
“…Because the differentiation of Th1 can antagonize the development of other types of Th cells, we speculate that the inhibitory effect on Gata-3 and ROR-␥t is not caused by IL-27, but by increased IFN-␥. Nevertheless, in PBMCs of normal controls, as reported by Sasaoka et al [37], IL-27 can inhibit the differentiation of Th17 cells. This difference between ITP patients and normal controls is attributed to the abnormal Th17 differentiation in ITP patients, but the exact mechanism requires further study.…”
Section: Discussionmentioning
confidence: 66%
“…Because the differentiation of Th1 can antagonize the development of other types of Th cells, we speculate that the inhibitory effect on Gata-3 and ROR-␥t is not caused by IL-27, but by increased IFN-␥. Nevertheless, in PBMCs of normal controls, as reported by Sasaoka et al [37], IL-27 can inhibit the differentiation of Th17 cells. This difference between ITP patients and normal controls is attributed to the abnormal Th17 differentiation in ITP patients, but the exact mechanism requires further study.…”
Section: Discussionmentioning
confidence: 66%
“…The exact role of IL-27 in CD remains to be elucidated. IL-27 can both promote and/or limit excessive Th1 response and inhibit Th17 cell differentiation, and, in murine studies of colitis, IL-27 has been associated with either promotion or attenuation of the disease, depending on the model (38)(39)(40)(41). Interestingly, human genetics studies identified polymorphisms and epigenetic modifications in p28 locus, suggesting that dysregulated p28/IL-27 production may contribute to CD pathology (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…The immune pathogenesis of TNBS-induced colitis is associated with increased levels of inflammatory cytokines, including IFN-g (46)(47)(48). Additionally, some inflammatory cytokines, such as IL-17 (32,49) and 50), play a crucial role in the induction of CD in patients and experimental colitis in mice. PON-1 inhibited the IFN-g production from both murine and human CD4 T cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental colitis was induced by the rectal administration of a TNBS solution in mice as described previously (32). Briefly, mice were anesthetized on day 0, and a silicon catheter was inserted intrarectally (i.r.…”
Section: In Vivo Experimental Design Of Tnbs-induced Colitis Experimentsmentioning
confidence: 99%